2014
DOI: 10.1177/0363546514557940
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Return to Sports and Work After Total Shoulder Replacement Surgery?

Abstract: Patients who participated in sports before TSA were successfully able to return to sports activities after surgery. Patients who did not participate in sports just before surgery were unlikely to start sports after surgery. Fourteen percent of the entire cohort was able to return to work after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 20 publications
3
81
1
2
Order By: Relevance
“…27 In a large study of 154 TSA patients, 14% returned to work, but specific jobs were not described in this analysis. 14 The results of this study suggest that more TSA patients successfully participate in low-demand activities, such as gardening or housework. Zarkadas and colleagues 18 reported that 65% of TSA and 47% of HA patients successfully returned to gardening compared with 42% of RSA patients observed in a continuation study.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…27 In a large study of 154 TSA patients, 14% returned to work, but specific jobs were not described in this analysis. 14 The results of this study suggest that more TSA patients successfully participate in low-demand activities, such as gardening or housework. Zarkadas and colleagues 18 reported that 65% of TSA and 47% of HA patients successfully returned to gardening compared with 42% of RSA patients observed in a continuation study.…”
Section: Discussionmentioning
confidence: 68%
“…Successful return to sports that involve shoulder function, such as golf and swimming, has been demonstrated for TSA. 8,14,16,17 However, studies have reported that return to these sports can be difficult for RSA patients. 20 Fink and colleagues 19 reported that following RSA, 48.7% of patients returned to moderate-intensity sports, such as swimming and golf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Reihe weiterer Studien aus den vergangenen 2 Jahren bestätigt die eher unerwartet gute Sportfähigkeit mit inversen Prothesen im kurz- bis mittelfristigen Verlauf mit bis zu über 90 % allgemeiner Rückkehrquote und 20-25 % Rückkehrquote sogar in High-impact-Sportarten binnen etwa 6 Monaten post-OP ohne erhöhte Komplikationsraten [68][69][70]. Für anatomische TEPs auf dem Boden einer primären Omarthrose konnten Bülhoff et al anhand einer Kohorte von n = 154 Patienten, stratifiziert nach präoperativer sportlicher Aktivität zeigen, dass 100 % der prä-OP aktiven Patienten (n = 105) auch post-OP wieder sportlich aktiv waren, während prä-OP inaktive Patienten (n = 49) auch post-OP sehr wahrscheinlich inaktiv bleiben [71]. Ähnliche Ergebnisse haben Schumann et al anhand 100 konsekutiver anatomischer TEP-Implantationen, darunter 55 Sportler, gefunden, wobei nach knapp 3 Jahren bei prä-OP aktiven Patienten, von knapp 90 % das ehemalige Sportniveau nahezu wieder erreicht wurde [66].…”
Section: Schulterendoprothetik: Allgemeine Sportfähigkeitunclassified
“…Eine Reihe weiterer Studien aus den vergangenen zwei Jahren bestätigt die eher unerwartet gute Sportfähigkeit mit inversen Prothesen im kurz-bis mittelfristigen Verlauf mit bis zu über 90 % allgemeiner Rückkehrquote und 20 -25 % Rückkehrquote sogar in High-impact-Sportarten binnen etwa 6 Monaten post-OP ohne erhöhte Komplikationsraten [68 -70]. Für anatomische TEPs auf dem Boden einer primären Omarthrose konnten Bülhoff et al anhand einer Kohorte von n = 154 Patienten, stratifiziert nach präoperativer sportlicher Aktivität zeigen, dass 100 % der prä-OP aktiven Patienten (n = 105) auch post-OP wie-der sportlich aktiv waren, während prä-OP inaktive Patienten (n = 49) auch post-OP sehr wahrscheinlich inaktiv bleiben [71]. Ähnliche Ergebnisse haben Schumann et al anhand 100 konsekutiver anatomischer TEP-Implantationen, darunter 55 Sportler, gefunden, wobei nach knapp 3 Jahren bei prä-OP aktiven Patienten, von knapp 90 % das ehemalige Sportniveau nahezu wieder erreicht wurde [66].…”
Section: Schulterendoprothetik: Allgemeine Sportfähigkeitunclassified